Changes in public administration along the Hungarian-Slovenian border in the 20th century - Mohos, Mária (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2003)
At the end of the 20th century the integration processes fastened in Europe. Between 1920-1990 the dividing role of the borders were dominant in Central-Europe, but in the last decade its bounding factor as well. The new borders of Hungary cut the previous administrational devices putting an end to the traditional cooperations. Along the Hungarian - Yugoslavian border mainly centralisation determined the changes of the administration system. The 1950 and 1970 laws and development concepts forced a lot of settlements to administrational units within which the development sources were located to the central settlements. The self government act was born in 1990 which allowed the settlements to create voluntary associations and separateness as well. Along the Prekmurje area given to Yugoslavia between the two World Wars the administrational centre was Muraszombat. In 1928 8 smaller devices were created, than in 1929 the Prekmurje are was enclosed to the Drava administrational area having Maribor as its centre. After the 2nd World War Muraszombat and Lendva functioned as centres up till 1999. In the separate Slovenian state at the end of the century a decentralized process started due to which new central units were organised.
Keywords: Hungary; Madžarska; Slovenia; Slovenija; obmejna območja; narodne manjšine; upravne enote; lokalna uprava; regije